2000
DOI: 10.1182/blood.v95.2.602
|View full text |Cite
|
Sign up to set email alerts
|

Soluble VCAM-1 binding to α4 integrins is cell-type specific and activation dependent and is disrupted during apoptosis in T cells

Abstract: Soluble vascular cell adhesion molecule-1 (sVCAM-1) is generated during inflammation and can alter lymphocyte functions. The authors report that the binding of sVCAM-1 to 4 integrin-bearing cells is a dynamically regulated, active cellular process. Binding of recombinant sVCAM-1 to 4 integrins on peripheral blood mononuclear cells was cell-type specific. Circulating CD16+ NK cells constitutively bound sVCAM-1 with high affinity, whereas a subpopulation of T-lymphocytes, primarily CD45RO+ (memory), bound sVCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 48 publications
1
37
0
1
Order By: Relevance
“…sVCAM-1 Blocks ␣4 Integrin-mediated Arrest. Soluble ligands bind high affinity integrin and inhibit high affinity but not high avidity adhesion (12)(13)(14). Therefore, accumulation assays were performed in the presence of sVCAM-1/ Fc to determine whether arrest and accumulation of flowing U937-FPR cells stimulated by coimmobilized FP or SDF-1␣ was dependent on very rapid upregulation of ␣4 integrin affinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sVCAM-1 Blocks ␣4 Integrin-mediated Arrest. Soluble ligands bind high affinity integrin and inhibit high affinity but not high avidity adhesion (12)(13)(14). Therefore, accumulation assays were performed in the presence of sVCAM-1/ Fc to determine whether arrest and accumulation of flowing U937-FPR cells stimulated by coimmobilized FP or SDF-1␣ was dependent on very rapid upregulation of ␣4 integrin affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Conformational changes affecting molecular structure and kinetic properties of individual bonds account for increased integrin affinity, whereas alignment and/or clustering of multiple receptor ligand pairs is the mechanism of high avidity-mediated adhesion (11,12). Soluble ligands bind high affinity integrins (13,14) and can be used to inhibit high affinity but not high avidity adhesion (12,13). Also, conformation-specific monoclonal antibodies may recognize neoepitopes present on high affinity integrins (15)(16)(17), although it is possible that they also recognize integrins stabilized by bound ligand (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Kitani et al [31] have shown that sVCAM-1 inhibits T cell proliferation possibly because of the suppression of IL-2 production. Rose et al [19] showed that sVCAM-1 could actively bind T cells but the binding is disrupted in apoptosis. This suggests that sVCAM-1 may be involved in adhesion and chemotaxis toward endothelium of circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major apoptotic pathways is the Fas ligand (FasL)/Fas pathway [12,13], in which caspase-3 is a key molecule in executing Fas-mediated apoptosis [14][15][16]. Soluble vascular cell adhesion molecule-1 (sVCAM-1) has been implicated in many vasculitis disorders [17,18] and leukocyte adhesion and migration [19]. Patients with SARS had lymphopenia [9] and extensive lung tissue damage [20].…”
Section: Introductionmentioning
confidence: 99%
“…VLA‐4 occurs in several activation and affinity states on resting leukocytes, and thus differentially contributes to tethering, rolling and firm adhesion of immune cells to VCAM‐1 3336. It has been previously reported by Rose et al that NK cells expressed VLA‐4 integrin that binds to VCAM‐1 with a higher affinity than VLA‐4 expressed on PBL 36. Similarly, we found that the chemokine CXCL12 triggered the arrest of NKT and NK cells on VCAM‐1 to similar levels and that they were dependent on high‐affinity VLA‐4.…”
Section: Discussionmentioning
confidence: 99%